2021
DOI: 10.1021/acsomega.1c00282
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Grade Inkjet Printer for Versatile and Precise Chemical Deposition

Abstract: Two simple, mechanical modifications are introduced to a consumer-grade inkjet printer to greatly increase its applicability. First, roller isolation bars are added to unlock multiple prints on the same substrate without smearing. This enables printing on a diverse set of substrates (rigid, elastic, liquid, granular, and sticky). Second, spring loadings are added to increase the print precision up to 50-fold, which facilitates alignment to a pre-patterned substrate or between successive prints. Utilizing the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…We observed that the ability to vary volumes via acceleration‐mode dip‐coating remains significant as the droplet base diameter is decreased, which means that the method likely also works for both smaller and larger footprints than the 50 µm to 6 mm range we have tested. This is important because the ability to create gradient arrays in a parallel manner becomes increasingly more important as droplets are scaled down, due to difficulties creating the droplets via other techniques (such as inkjet printing, [ 29 ] even when acoustophoretic printing is employed [ 30 ] ) and the large number of droplets makes it time‐consuming to produce them drop‐by‐drop.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the ability to vary volumes via acceleration‐mode dip‐coating remains significant as the droplet base diameter is decreased, which means that the method likely also works for both smaller and larger footprints than the 50 µm to 6 mm range we have tested. This is important because the ability to create gradient arrays in a parallel manner becomes increasingly more important as droplets are scaled down, due to difficulties creating the droplets via other techniques (such as inkjet printing, [ 29 ] even when acoustophoretic printing is employed [ 30 ] ) and the large number of droplets makes it time‐consuming to produce them drop‐by‐drop.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the printing methods, inkjet printing, a digital manufacturing technique renowned for its precision, versatility, and scalability, offers the potential to create customized drug delivery devices with unparalleled precision in drug loading and spatial distribution. It could not only customize and tailor drug dosages according to the specific needs of a patient [ 80 , 81 ] but also allow drug delivery systems with specific release profiles [ 82 , 83 ], such as delayed or sustained release, as shown in Fig. 6 A.…”
Section: Emerging Biomedical Advancesmentioning
confidence: 99%
“…This is of importance in scenarios where a gradient of drug concentration (as demonstrated in Fig. 6 B) or co-delivery of multiple therapeutics in defined ratios can enhance therapeutic outcomes [ 81 ].
Fig.
…”
Section: Emerging Biomedical Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomedical additive manufacturing is gaining popularity for low-cost prototyping and manufacturing due to its advantages in noncontact printing, speed, and accuracy. Recently, droplet-based two-dimensional (2D) and three-dimensional (3D) printing techniques like inkjet printing have become hot research focus for appropriate pharmaceutical applications, allowing the creation of personalized medicine and targeted drug delivery system through automated control over drug doses and releases, making the vision of patient-specific treatment on the horizon tangible reality. ,, However, further exploration and optimization are needed to fully utilize the capabilities of droplet-based 2D and 3D printing techniques in healthcare applications. One of the main challenges associated with droplet-based printing techniques in the preparation of personalized medicines is the development of pharmaceutical inks (similar to bioinks in bioprinting) with suitable mechanical characteristics and adjustable drug release time. ,, Pharmaceutical inks are meticulously formulated inks that contain drugs and excipient substances.…”
Section: Introductionmentioning
confidence: 99%